(untitled) (Handbook of Treatment Algorithms for Medical and Pharmacy Students, 2025)
Author Mrs. Udaya Kumari Tula, Research Associate Scientist, DSK Biopharma Inc. Pharmaceutical Company, Morrisville, North Carolina, USA Abstract Dermatologic treatment algorithms are organized by etiology and clinical morphology. The algorithm for common skin infections is etiology-specific. Bacterial infections like cellulitis are treated with systemic antibiotics targeting Gram-positives, whereas superficial impetigo responds to topical mupirocin. Fungal infections (tineas) are managed with an algorithm progressing from topical azoles or terbinafine to oral terbinafine or fluconazole for extensive disease or onychomycosis. Viral infections like HSV require episodic or suppressive oral antivirals (e.g., valacyclovir). Autoimmune skin disorder algorithms aim for inflammation control. Plaque psoriasis follows a stepwise algorithm from high-potency topical corticosteroids and vitamin D analogs, to phototherapy, and finally to systemic agents or biologics for moderate-to-severe disease. Bullous pemphigoid management prioritizes high-potency topical or systemic corticosteroids. Dermatitis algorithms are centered on barrier repair and inflammation suppression. Atopic dermatitis is managed with a foundational algorithm of emollients, followed by topical corticosteroids or calcineurin inhibitors. Skin cancer algorithms are dictated by tumor type and risk. Basal cell and squamous cell carcinomas are treated with an algorithm based on location and risk, primarily surgical excision or Mohs micrographic surgery. Melanoma management is a stage-dependent algorithm involving wide local excision, sentinel node biopsy for staging, and systemic immunotherapy or targeted therapy for advanced, metastatic disease Keywords: Dermatitis, Psoriasis, Skin Infections, Skin Cancer, Melanoma, Treatment Algorithm VIEW PDF